ECONOMIC DEVELOPMENT IN THE ERA OF ḤAZRAT ʿUMAR ʾIBN KHATTAB RA: AN ILLUMINATION FOR THE CONTEMPORARY - Javeria Azkar; Talal Nawaz Janjua; Muhammad Ilyas (Journal of Religion and Society, 2025)
Abstract: Ḥazrat ʿUmar ʾibn Khattab RA was the second rightly guided Caliph of Islam. He was one of the extraordinary personalities in the history of Islam. He was the greatest man of all time, a benevolent administrator, a great conqueror, a just ruler, and a founder of the Muslim empire. The highlight of his financial policy and reforms is establishing a Diwan, refining the functionalities of the State’s treasury also known as Bait-ul-Maal. Ensuring effective tax imposition, maintaining records of beneficiaries and taxpayers, collection of Zakat, Khiraj, Jizya, Ushr, war booty, and systematic disbursements of all collected funds. Reforming the entire framework of the economy and dealing with the opposition arising after passing any new legislation in the finance department. This article explores in-depth the entire monetary structure in the Caliphate of Ḥazrat ʿUmar ʾibn Khattab RA. Keywords: Umar, Wealth, Economy, Zakat, Khiraj, Ushr, Divan, Bait-ul-Maal, Stipends, Expenditure, Treasury.